2008
DOI: 10.1007/s00192-008-0737-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in connective tissue in patients with pelvic organ prolapse—a review of the current literature

Abstract: Little is known about the pathophysiology of pelvic organ prolapse (POP). In 1996, Jackson presented a hypothesis on pelvic floor connective tissue that tried to explain the development of POP on a molecular level. The objective of this review is to test the hypothesis against recent literature. The method used was a review of literature. The association between POP and connective tissue metabolism is well established. However, the causality of this association is unclear. The characteristics of the pelvic flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
173
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(186 citation statements)
references
References 99 publications
5
173
0
8
Order By: Relevance
“…Type III collagen is also the first type of collagen involved in wound repair and fibrosis, before it is replaced by collagen I. [20][21][22] Several studies have compared the amount of total and individual subtypes of collagen in the supporting ligaments and vaginal tissue of women with POP to a control group (see Table 1). 19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] Figure 1 Current anatomical considerations for prolapse.…”
Section: Collagen Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type III collagen is also the first type of collagen involved in wound repair and fibrosis, before it is replaced by collagen I. [20][21][22] Several studies have compared the amount of total and individual subtypes of collagen in the supporting ligaments and vaginal tissue of women with POP to a control group (see Table 1). 19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] Figure 1 Current anatomical considerations for prolapse.…”
Section: Collagen Compositionmentioning
confidence: 99%
“…Fibroblasts are mechanoresponsive, modifying their actin cytoskeleton when stretched. This results in poor contractility and decreased functionality after stretch, as reviewed by Kerkhof et al, 20 Women with prolapse have reduced density of fibroblasts in the uterosacral ligaments and paravaginal fascia. 23 Several studies have also demonstrated modified fibroblast responses in prolapse.…”
Section: Regulators Of Collagenmentioning
confidence: 99%
“…The pelvic fl oor is the lower border of the abdomen and it refrains the pelvic organs from prolapsing, via two main mechanisms: pelvic fl oor muscle contraction and the vaginal ligaments that are anchored on the bony pelvis. The collaboration of these two confers the normal function to the pelvic fl oor during coitus, labour, urination and defecation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Parity, aging, and a chronic increase in abdominal pressure have been proven to be predisposing factors in the development of pelvic floor disorders ). There has also been growing evidence to support the role of genetics and disturbances in the extracellular matrix in the development of POP and UI Kerkhof et al, 2009;Reisenauer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Human studies have revealed a marked decrease and fragmentation of elastin fibers in patients with POP (Kerkhof et al, 2009;Reisenauer et al, 2008). Abnormal elastin homeostasis was also noted in women with stress UI (Soderberg et al, 2009;Goepel and Thomssen, 2006;Wen et al, 2007;Chen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%